Teaching in the digital frontier: what drives metaverse adoption in education? - Cassandra, Cadelina; Masrek, Mohamad Noorman; Aman, Fadhilah (International Journal of Evaluation and Research in Education (IJERE), 2025)
The rapid evolution of digital technologies has caused dramatic changes in various areas, including education. Metaverse has become a very popular topic recently, many schools and university announce the development of metaverse, but until now there is no clear implementation of the idea and some schools cancelled to continue the implementation. One of the reasons behind it because of the lack of preparedness, reluctant from teachers, and there is no initial investigation about how the teachers will accept this technology. Several factors may influence the intention of the teachers. The purpose of this study is to analyze the factors that affect high school teachers’ intentions to use metaverse technology. By doing so, the institution can prepare for the real implementation. This study employs quantitative methods and survey techniques by developing a well-structured questionnaire from the theoretical framework. A total of 334 responses were collected and analyzed using SmartPLS software. The findings reveal that 14 hypotheses out of 18 hypotheses were significant and four others were not significant. Social influence (SI), performance expectancy (PE), effort expectancy (EE), and facilitating condition (FC) positively influence teachers’ behavioral intention (BI) to use metaverse applications. On the flip side, personal innovativeness (PI) does not significantly impact performance and EE. Trialability (TR) and corporeity (CR) also do not influence EE. However, hedonic motivation (HM), compatibility (CO), TR, interactivity (IN), and persistence are significant factors for performance and EE.